Moodle-Based Learning Model for Paragraph Writing Class - Wulandari, Mega (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2015)
Todays language classroom is vastly different from that of the twentieth century. The trends in language learning are moving forward in a way as to empower language learners to interact with others. Time and place boundaries are transcended by internet-based media to facilitate the interaction they are eager to make. Language teachers must now be able to utilize internet for language learning, especially in writing class because most learners assume that writing skill is the hardest part of language to learn, which require learners to practice intensively in order to gain mastery. Moodle (Modular, Object-Oriented, Dynamic, and Learning Environment) is one of many internet-based media through which teachers can work with students, whether in distance mode or as a supplement to face-to-face teaching. There are four basic things teachers and students can do with Moodle, namely: storing, communicating, collaborating, and evaluating. Considering those potentials, this research aimed at developing a Moodle learning model of Paragraph Writing at the university level. The result of the research was the theoretical model and the iconic Moodle learning model. The theoretical model presents the Moodle features that were selected according to their suitability with the theory of paragraph writing as well as with the CALL principles and Gagnes nine events of instruction. The iconic model was developed by making some revisions based on the results of the expert validation and the user validation. The iconic learning model could be accessed on www.writing2pbi.mdl2.com.